Pregnancy and the Postpartum Period in Women With Relapsing-Remitting Multiple Sclerosis Treated With Old and New Disease-Modifying Treatments: A Real-World Multicenter Experience - Zanghì, Aurora; D'Amico, Emanuele; Callari, Graziella; Chisari, Clara Grazia; Borriello, Giovanna; Grimaldi, Luigi Maria Edoardo; Patti, Francesco (Frontiers in Neurology, 2020)
Introduction: Trends of disease activity during pregnancy, the postpartum period, and until 24 months from the delivery in the era of new drugs for the treatment of relapsing-remitting multiple sclerosis (RRMS) need to be investigated. Methods: In this cross-sectional Italian multicenter study, women with RRMS were included; the disease-modifying treatment (DMT) at the time of conception included were: interferons, glatiramer acetate, teriflunomide, dimethyl fumarate, fingolimod, and natalizumab. The main outcome of the study was to determine the rate of relapse occurrence during pregnancy and the postpartum period in all women grouped for each DMT. The secondary outcome was to determine the overall disease activity assessed by NEDA 3 (relapse, disability level, and radiological activity) at 24 months from the date of delivery. Results: Completed data were available for 81 pregnancies (in 74 women). Women on interferons and glatiramer had longer disease duration than women on dimethyl fumarate, fingolimod, and natalizumab (p < 0.05). Overall, we recorded 25 relapses during pregnancy (11 in 11 women) and the postpartum period (14 in 14 women). Natalizumab was the most commonly DMT in women (3) who experienced relapses during pregnancy. IFNs were the most commonly prescribed DMT in women (8) who experienced relapses during the postpartum period. At logistic regression analysis, specific treatment per se was not associated with relapse occurrence. No differences among the DMTs groups were recorded about NEDA 3 status at 24 months of follow-up. Conclusions: In our population, there was no difference in terms of relapses occurrence, disability status, and the overall disease activity during a follow up of 24 months.